The Impact of Multi-Nozzles Array on Entrainment Mass Flow Rate and Homogeneity of the Speed and Profiles of Heat - ., Sarjito; Marchant, Denis; Yao, Yufeng; ., Binyamin (International Journal of Engineering and Technology, 2019)
The aims of the research work described in this paper are to use computational fluid dynamics (CFD) to investigate the impact of the downdraught mass flow rate generated and the homogeneity of the speed and heat profiles downstream of the multi- nozzles array. This included a work to define the optimum number, and the most effective arrangement of spray nozzles in a multi-nozzle array. Two different basic arrangements of the nozzles were studied; one in which a constant radius of 0.75 m was kept for the nozzle pitch circle as nozzles were added, and another, in which a constant distance of 0.75 m was guarded between all nozzles.Â A second simulation was set up using the configuration with constant spacing but with a single central nozzle embedded.Â A final simulation was carried out to determine if further optimization of the nozzle configuration could be obtained by altering the constant nozzle spacing in the range 0.35 to 0.85 m.Â Based on these simulations, it was determined that constant spacing provided greater cooling with fewer nozzles than the configurations with constant radius.Â Furthermore, it was found that the arrangement with 11 nozzles, with a nozzle spacing of 0.65 meters, gave the optimum overall performance.Â Â